2015
DOI: 10.14214/sf.1056
|View full text |Cite
|
Sign up to set email alerts
|

Seed soak-sorting prior to sowing affects the size and quality of 1.5-year-old containerized <i>Picea abies</i> seedlings

Abstract: Seed soak-sorting prior to sowing affects the size and quality of 1.5-year-old containerized Picea abies seedlings Himanen K., Nygren M. (2015). Seed soak-sorting prior to sowing affects the size and quality of 1.5-year-old containerized Picea abies seedlings. Silva Fennica vol. 49 no. 3 article id 1056. 14 p. Highlights• After soak-sorting all sunken seeds (bottom fraction) were full and viable, whereas floating seeds contained larvae-filled and immature seed.• Seedlings originating from the bottom fraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1A. Applying this widely used "float-testing", viable seeds stay fully immersed in water as a result of the higher weight caused by the presence of germen, while nonviable seeds (empty or without germen) stays floating in the surface (Himanen & Nygren, 2015). Viable ( Fig.…”
Section: Plant Materialsmentioning
confidence: 99%
“…1A. Applying this widely used "float-testing", viable seeds stay fully immersed in water as a result of the higher weight caused by the presence of germen, while nonviable seeds (empty or without germen) stays floating in the surface (Himanen & Nygren, 2015). Viable ( Fig.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The quality and germinability of seeds greatly influence the success of producing healthy and well-growing seedlings. Germinability and seedling health can be enhanced through different production methods [8]. In this issue, Kaliniewicz and Tylek [9] found that the quality of pedunculate oak acorns can be improved by different seed treatments prior to germination.…”
mentioning
confidence: 99%
“…In addition, up to 58 % of mature juniper fruits are attacked by Megastigmus insect species, resulting in germination failure (Djavanshir 1974). These unproductive seeds should be removed from the seed lots to produce the desired quantity of seedlings needed for active restoration program and for ensuring a high percentage of usable seeds in nurseries (Himanen and Nygren 2015) to reduce the cost of containerized seedling production.…”
Section: Introductionmentioning
confidence: 99%
“…Willd seed lot. Using SG separation in water, Himanen and Nygren (2015) effectively sorted nonviable seeds of Picea abies L. (Karst.…”
Section: Introductionmentioning
confidence: 99%